SPATIAL MODELING OF LAND COVER DYNAMICS IN DKI JAKARTA CILIWUNG WATERSHED USING CA-MARKOV APPROACH - Mohamad Mahfudz; Baba Barus; Asep Sapei; Bambang Pramudya Noorachmat (GeoEco, 2026)
Land use and land cover (LULC) change driven by human activities has become a major factor influencing environmental dynamics, particularly in rapidly urbanizing areas. This study aims to analyze LULC changes in the Ciliwung Watershed, DKI Jakarta, during the period 2010–2025 and to project future trends up to 2030. The study utilizes Landsat imagery with a spatial resolution of 30 meters, combined with a Geographic Information System (GIS) approach and the Cellular Automata–Markov (CA-Markov) model. LULC classification was categorized into six classes, achieving an overall accuracy of 80% and a Kappa coefficient above 75%, indicating strong agreement. The results show a significant increase in built-up areas by 81.83% by 2030, accompanied by a decrease in open land by 18% and forest areas by 13.53%. Agricultural land and shrubland show slight increases of 1.57% and 0.82%, respectively, while water bodies remain relatively stable at 2.07%.  The expansion of built-up areas exerts considerable pressure on green spaces and reduces water infiltration capacity, thereby increasing the potential risk of flooding in the study area. These findings highlight the importance of implementing adaptive and sustainable spatial planning policies to control LULC changes and mitigate future environmental impacts.